Pete the cat's got class - Dean, James 1957- (Harper, 2016)
When he sees his friend Tom struggling with adding and subtracting, Pete the Cat has an idea to help
Keywords: Pete / the Cat (Fictitious character) / Juvenile fiction; Pete / the Cat (Fictitious character); Cats / Juvenile fiction; Arithmetic / Juvenile fiction; Homework / Juvenile fiction; Helping behavior / Juvenile fiction; Schools / Juvenile fiction; Arithmetic; Cats; Helping behavior; Homework; Schools; Cats / Fiction; Mathematics / Fiction; Schools / Fiction; Mathematik; Bilderbuch